Evaluasi Kebijakan Peraturan Baznas Nomor 2 Tahun 2016 Tentang Pembentukan Dan Tata Kerja Unit Pengumpul Zakat Di Universitas Padjadjaran - Nanang Suparman; Wildan Romadhon (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2019)
This study aims to find out and describe the process of implementing the UPZ implementation policy evaluation at Padjadjaran University: Factors that have constrained the evaluation of UPZ policies at Padjadjaran University: and the implications of the constraints on the existence of UPZ Padjadjaran University. This study uses a policy evaluation theory from William. N. Dunn who said that policy evaluation is influenced by six dimensions. The research method used is a qualitative approach with a type of descriptive method. Techniques for collecting data through interviews, observation, and literature. Based on the results of the study, it was found that the policy evaluation of the Central Baznas Regulation Number 2 of 2016 had not yet run optimally. This is because there are still among Muzaki who have potentially not participated in the UPZ Unpad and mustahik who have not all felt satisfied with the service and provision of infaq and charity zakat funds. In addition, the human resources available at UPZ Unpad are still limited, especially in the ranks of the management.